Mining metagenomic whole genome sequences revealed subdominant but constant Lactobacillus population in the human gut microbiota. Issue 3 (12th May 2016) - Rossi, Maddalena; Martínez‐Martínez, Daniel; Amaretti, Alberto; Ulrici, Alessandro; Raimondi, Stefano; Moya, Andrés
Summary: The genus Lactobacillus includes over 215 species that colonize plants, foods, sewage and the gastrointestinal tract (GIT) of humans and animals. In the GIT, Lactobacillus population can be made by true inhabitants or by bacteria occasionally ingested with fermented or spoiled foods, or with probiotics. This study longitudinally surveyed Lactobacillus species and strains in the feces of a healthy subject through whole genome sequencing (WGS) data‐mining, in order to identify members of the permanent or transient populations. In three time‐points (0, 670 and 700 d), 58 different species were identified, 16 of them being retrieved for the first time in human feces. L. rhamnosus, L. ruminis, L. delbrueckii, L. plantarum, L. casei and L. acidophilus were the most represented, with estimated amounts ranging between 6 and 8 Log (cells g −1 ), while the other were detected at 4 or 5 Log (cells g −1 ). 86 Lactobacillus strains belonging to 52 species were identified. 43 seemingly occupied the GIT as true residents, since were detected in a time span of almost 2 years in all the three samples or in 2 samples separated by 670 or 700 d. As a whole, a stable community of lactobacilli was disclosed, with wide and understudied biodiversity.